Drugs, Patents, and Well-Being - Christopher Buccafusco; Jonathan S. Masur (Washington University Law Review, 2021)
The ultimate end of patent law should be to spur innovations that improve human welfare—innovations that make people better off. But firms will only invest resources in developing patentable inventions that will allow them to make money—that is, inventions that people will want to use and buy. This can gravely distort the types of incentives that firms face and the types of inventions they pursue. Nowhere is this truer than in the pharmaceutical field. There is by now substantial evidence that treatments for diseases that primarily afflict poorer people—including the citizens of developing nations—are dramatically underproduced, compared with drugs that treat diseases that afflict the wealthy. In addition, the pharmaceutical markets are rife with “me too” drugs—drugs that treat diseases or conditions for which successful medications already exist. This state of affairs is not inevitable. In recent years, medical and psychological research on well-being has created the capacity for policymakers to draw direct links between patents and human welfare. Armed with this information, policymakers have, for the first time, the power to use the patent system to directly incentivize welfare-enhancing innovations. In this Article, we propose a system of extended patent terms for drug inventions that have a significant impact on human welfare. We further propose that policymakers lift many of the legal protections for patents that have an insubstantial effect on human welfare—which we term “futility patents”—making those patents easier to challenge and invalidate. The result would be a reorientation of pharmaceutical firm incentives toward drugs that will have a significant impact on welfare, particularly for poorer and underserved populations, and away from drugs that are profitable but do little to improve human life.
Keywords: Patent law; Futility patents; Pharmaceutical patents; Welfare-Enhancing drugs; Intellectual property law